Scientific Learning Approach on Subject Material Computer Application for Financial Administration - Saeroji, Ahmad; Slamet, Achmad; Khafid, Muhammad (Journal of Economic Education, 2018)
Through the 2013 curriculum as a transition from the Education Unit Level curriculum (KTSP) 2006 into a real effort of the government to improve the education process in Indonesia , in the 2013 curriculum with the learning system of students are told to be the students of the tofu. 2013 curriculum is a scientific approach , a scientific approach is a learning process approach using 5M syntax (Observing, Asking, Gathering Information, Associating / Reasoning and Communicating). The subject of Financial Administration is one of the new subjects in Vocational High School Administration Expertise Program on the Basic Competencies of Computer Applications for Financial Administration. The application of a scientific approach is only included as one of the administrative requirements in the Lesson Plans.The purpose of this research is to know the application of scientific approach with 5M syntax (Observing, Asking, Collecting Information, Associating / Reasoning and Communicating) by describing the activity of each 5M syntax on Financial Administration Subjects Administration Program Administration Class XII SMK Negeri 9 Semarang Year Lesson 2017/2018. This research is a qualitative research.Data collection is done by observation, interview, and documentation.The results showed that in the learning activity deangan scientific approach by using 5M syntax is done well but in one meeting not all sync 5M activities, but the 5M syntax is divided into several meetings on core learning activities, because the learning in every meeting consists of opening activities, core and cover. The 5M syntax scientific approach is carried out in Core activities.